2015
DOI: 10.1002/lno.10047
|View full text |Cite
|
Sign up to set email alerts
|

Model-based interpretation of sediment concentration and vertical flux measurements in a shallow estuarine environment

Abstract: A one-dimensional numerical model describing tidally varying vertical mixing and settling was used to interpret sediment concentrations and vertical fluxes observed in the shoals of South San Francisco Bay by two acoustic Doppler velocimeters (ADVs) at elevations of 0.36 m and 0.72 m above bed. Measured sediment concentrations changed by up to 100 g m 23 over the semidiurnal tidal cycle. These dynamics were dominated by local resuspension and settling. Multiple particle class models suggested the existence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 46 publications
4
15
1
Order By: Relevance
“…Our measurements were conducted at shear velocities of up to 0.65 cm s -1 , which is 5-10 times lower than the ones reported by Nikora and Goring [2000]. Still, typical critical shear velocities of cohesive muddy sediments range between 0.5 and 1 cm s -1 [Brand et al, 2015;Sanford and Halka, 1993] and are therefore close to the shear velocity observed in our study. On the other hand, we did not observe the expected reduction in the von K arm an constant due to bed motion reported by Nikora and Goring [2000] which suggests that there is no occurrence of a moving bed in our study.…”
Section: Mixing Coefficients Energy Production and Velocity Fluctuatsupporting
confidence: 73%
See 1 more Smart Citation
“…Our measurements were conducted at shear velocities of up to 0.65 cm s -1 , which is 5-10 times lower than the ones reported by Nikora and Goring [2000]. Still, typical critical shear velocities of cohesive muddy sediments range between 0.5 and 1 cm s -1 [Brand et al, 2015;Sanford and Halka, 1993] and are therefore close to the shear velocity observed in our study. On the other hand, we did not observe the expected reduction in the von K arm an constant due to bed motion reported by Nikora and Goring [2000] which suggests that there is no occurrence of a moving bed in our study.…”
Section: Mixing Coefficients Energy Production and Velocity Fluctuatsupporting
confidence: 73%
“…It governs the transfer of solutes to and from the sediment [Brand et al, 2008;Bryant et al, 2010], which in turn feeds back on microbial dynamics and reaction kinetics [Brand et al, 2009;Frindte et al, 2013]. Resuspension of particles, which can significantly enhance mineralization reactions and nutrient turnover in marine [Cloern, 1987;Tengberg et al, 2003] as well as in limnetic systems [Kleeberg et al, 2008], is also governed by the fluid flow close to the SWI [Brand et al, 2015]. In lakes with a pronounced thermocline, bottom boundary layer turbulence generated by bottom shear can be the main source of vertical mixing [Goudsmit et al, 1997] even though this mixing can be highly intermittent [Brand et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we set the same fq,j throughout the simulation for each bed layer, which is based on the observation that the floc size distribution in the water column strongly depends on flow conditions (Manning & Schoellhamer, ) due to flocculation and breakup processes, rather than the grain size distribution in the bed. The same idea was adopted by Brand et al (), who modeled SSC at a single point in South Bay using a one‐dimensional vertical (1‐DV) with two sediment size classes. In their model, the settling velocities, fraction of each class, and total erosion rate are obtained from the flux and concentration measurement above the sediment bed.…”
Section: Model Descriptionmentioning
confidence: 99%
“…Based on a comparison between the measured SSC at different sites, Brand et al () also show strong spatial variability of SSC in South Bay. To model the SSC at a shallow shoal in South Bay, a one‐dimensional vertical (1−DV) model was proposed by Brand et al () which models vertical turbulent mixing and settling of two sediment size classes. After calibrating the settling velocity of a “fast‐settling” size class and a “slowly settling” size class, the approach gives good predictions of SSC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation